Utilization of Front Roll Gymnastics Audio Visual Media to Improve Students' Learning Outcomes - Mas Jaya, Andi; Dos Santos, Hezron Alhim; Nur Linda, Ince (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to improve the learning outcomes of forward rolls of class VIII A students of SMPN 1 Turikale Maros using audio visual media. This type of research is a type of classroom action research (CAR). The research was conducted for two cycles. Each meeting used a research procedure consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 29 students of class VIII A of SMPN 1 Turikale Maros. The research instruments used were observation, evaluation tests, field notes and documentation. While the data collection technique used observation techniques, test techniques, and documentation.